Resposta :
Resposta:
a) 47
b) 9
c) 42
d) 1
e) 1
Explicação passo-a-passo:
a) 38+{35-[7+(15-5)+9]}=
38+{35-[7+10+9]}=
38+{35-[17+9]}=
38+{35-26}=
38+9=
47
b) {75-[44+(13-5)+2]-10}-2=
{75-[44+8+2]-10}-2=
{75-[52+2]-10}-2=
{75-54-10}-2=
{21-10}-2=
11-2=
9
c) {[(60-30)-20]+20}+12=
{[30-20]+20}+12=
{10+20}+12=
30+12=
42
d) 10-{[(3+8)-4]+2}=
10-{[11-4]+2}=
10-{7+2}=
10-9=
1
e) 17+{[25-(14-8)+(6-4)]-5}=
17+{[25-6+(6-4)]-5}=
17+{[25-6+2]-5}=
17+{[19+2]-5}=
17+{21-5}=
17+16=
1
Por favor coloca como melhor resposta, obrigada. Espero ter ajudado S2.